Mechanizmy pamięci i zapomnienia w kulturze muzycznej Śląska: Caspar Neumann (1648–1715) i recepcja pieśni "Liebster Gott, wenn werd ich sterben"? - Joachimiak, Grzegorz (Res Facta Nova, 2025)
This article explores the Silesian hymnal compiled by Caspar Neumann (1648–1715) in relation to the circulation of the hymn Liebster Gott, wenn werd ich sterben? in the seventeenth and eighteenth centuries. Drawing on manuscripts and prints from Lutheran, Reformed, and Catholic contexts, it analyses textual stability alongside melodic variation, visualised through a map of geographical dispersion. The study highlights Neumann’s editorial strategy of reducing and systematising the repertoire, which may be understood as a mechanism of memory management, balancing processes of selection, remembering, and forgetting. Particular attention is given to the hymn’s eschatological profile – its associations with memento mori, ars moriendi, and funeral preaching – showing how it functioned in both communal worship and domestic devotion. The results position Silesia as a mediator of Central European hymn traditions and demonstrate how a single hymn could sustain diverse local adaptations while retaining its theological and emotional core. By linking musical variants with cultural memory and strategies of repertoire curation, his article offers a new perspective on the dynamics of early modern religious song.